1991
DOI: 10.1080/0924345910020303
|View full text |Cite
|
Sign up to set email alerts
|

Improving Instructional and Classroom Management Skills: Effects of a Staff Development Programme and Coaching

Abstract: This article presents the results of a school improvement study (main field test) directed at schools with mixed-age classes in the context of in-service teacher education. A quasi-experimental treatment-control group investigation was designed to test the effects of the staff development programme 'Dealing with Mixed-age Classes,' and the effects of coaching in addition to the programme. Based on pre-and post-training classroom observations, a significant treatment effect was found for pupil's time-ontask lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Based on pretraining and posttraining classroom observation, these studies revealed a significant treatment effect for the time-on-task levels of the students in the multigrade classes and for the instructional and management skills of the teachers. However, no significant differences in achievement were found between the students in classes with trained multigrade teachers and the students in classes with untrained single-grade teachers (Roelofs, 1993;Roelofs, Raemaekers, & Veenman, 1991;Roelofs, Veenman, & Raemaekers, 1994;Veenman & Raemaekers, 1995).…”
Section: Veenmanmentioning
confidence: 91%
“…Based on pretraining and posttraining classroom observation, these studies revealed a significant treatment effect for the time-on-task levels of the students in the multigrade classes and for the instructional and management skills of the teachers. However, no significant differences in achievement were found between the students in classes with trained multigrade teachers and the students in classes with untrained single-grade teachers (Roelofs, 1993;Roelofs, Raemaekers, & Veenman, 1991;Roelofs, Veenman, & Raemaekers, 1994;Veenman & Raemaekers, 1995).…”
Section: Veenmanmentioning
confidence: 91%
“…In addition, a questionnaire representing the use of direct instruction was developed, based on scales used in previous studies (Roelofs, Raemaekers & Veenman, 1991;Roelofs, Veenman & Raemaekers, 1994). The resulting scale (14 items, α = 0.79) can be considered as an indicator of a transmission-oriented learning environment in which many activities, including constructing meaning, are in essence teacher-led.…”
Section: Design Of Learning Environmentsmentioning
confidence: 99%
“…Each of these explanations fall short of giving combination class teachers credit for handling, by all accounts, a highly complex and demanding learning environment that involves a wide range of students, two curriculums, two instructional presentations, two evaluation systems, and numerous scheduling and classroom management problems. Finally, we wonder just how much training combination teachers would need to improve their student achievement, given that an apparently well-developed training program used by Veenman and his colleagues (Roelofs, 1993;Roelofs, Raemaekers, & Veenman, 1991;Roelofs, Veenman, & Raemaekers, 1994;Veenman & Raemaekers, 1995) did not raise achievement above that of single-grade classes with untrained teachers.…”
Section: Explanation Of the Finding Of No Difference In Achievementmentioning
confidence: 99%